Prospek Kontrasepsi Pria dalam Pengendalian Pertumbuhan Penduduk melalui Pendekatan Molekular - Putri Rahayu Ratri; Mira Andriani (Puslitbang Sinergis Asa Professional, 2020)
Nowadays, developing contraception methods were mostly addressed to women. The development of male contraception was still limited. There were condoms, vasectomies, and interrupted intercourse, which used in male contraception. The condom method and interrupted intercourse have a high failure rate and inconvenience in its use. The vasectomy method is invasive and expensive. The development of molecular-based contraceptive methods with minimal impacts on health is expected to be a good breakthrough in the context of population control and improving the quality of health. The study aims to summarize and analyze the early development of contraception until the invention of molecular contraception through immunologic, proteomic, and metabolomics science. This article review was done by studying literature in the PubMed Central (PMC), Springer, and Open Access ScienceDirect databases. The search was performed with the keywords